1990
DOI: 10.1007/bf00019156
|View full text |Cite
|
Sign up to set email alerts
|

A low molecular weight DNA polymerase from wheat embryos

Abstract: The study of plant DNA polymerases lags far behind that concerning their animal or yeast counterpart. In this work we describe the first extensive purification to apparent homogeneity, as well as a detailed biochemical and immunological characterization, of a low molecular weight DNA polymerase (DNA polymerase CI) purified from wheat embryos. The monomeric enzyme is a basic protein having a molecular weight of 52 kDa. Polyclonal antibodies raised in rabbits against DNA polymerase CI did not inhibit animal DNA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

1992
1992
2012
2012

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 39 publications
0
15
0
Order By: Relevance
“…Either wheat germ or wheat embryos (4-8 g) were used. Ammonium sulfate fractionation, and purification by phosphocellulose, DEAE cellulose and MonoS chromatography were performed as described before [6].…”
Section: Wheat Dna Polymerase Purificationmentioning
confidence: 99%
See 1 more Smart Citation
“…Either wheat germ or wheat embryos (4-8 g) were used. Ammonium sulfate fractionation, and purification by phosphocellulose, DEAE cellulose and MonoS chromatography were performed as described before [6].…”
Section: Wheat Dna Polymerase Purificationmentioning
confidence: 99%
“…In our laboratory, four wheat germ DNA polymerases from nuclear origin, named A, B, CI and CII, have been purified and characterized [4,6,29]. A comparative analysis of their biochemical properties with mammalian DNA polymerases does not show a strong similarity between plant and animal systems.…”
Section: Introductionmentioning
confidence: 99%
“…The detailed purification procedures of DNA primase (Laque1 et al, 1990a) and DNA polymerases A, B, (31, and CII have been published previously (Castroviejo et al, 1979(Castroviejo et al, , 1991Lalquel et al, 1990b;Richard et al, 1991).…”
Section: Purificatiion Of Wheat Dna Primase and Wheat Dlna Polymerasesmentioning
confidence: 99%
“…We found that DNA polymerase CII has some properties of DNA polymerase a, whereas DNA polymerase B is very similar to DNA polymerase 6, since it is highly resistant to butyl-phenyl dGTP and possesses a 3'-5' exonuclease activity (Richard et al, 1991). DNA polymerase CI is similar to animal DNA polymerase p: it is the only low mo1 wt DNA polymerase in wheat and it is resistant to aphidicolin and highly sensitive to ddTTP (Castroviejo et al, 1991). DNA polymerase A is an difficult enzyme to classify and shows some properties of DNA polymerase y (Tarrago-Litvak et al, 1975).…”
mentioning
confidence: 99%
“…The presence of DNA polymerase a (POLA) activity in plants has been shown biochemically in maize, wheat, pea, and cauliflower (Bryant 1980;Castroviejo et al 1990;Laquel et al 1990;Balmukhanovet al 1992;Bryant et al 1992;Coello et al 1992;Coello and Vazquez-Ramos 1995b;Garcia et al 1997;Luque et al 1998). More recently, the genome sequence analysis of Arabidopsis and rice allowed the identification of the four putative subunits of POLA complex (POLA1 to 4).…”
Section: Polamentioning
confidence: 99%